2014
DOI: 10.2355/isijinternational.54.2907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur Content on Inclusion and Microstructure Characteristics in Steels with Ti2O3 and TiO2 Additions

Abstract: The effect of the sulfur content on the inclusion and microstructure characteristics of steels where Ti2O3 and TiO2 have been added was studied. Based on the microscopic examinations, it is found in the steel samples with Ti2O3 additions that the area fraction of intragranular ferrite decreases from 52.68% to 39.09% as the sulfur content increases from 0.009 mass.% to 0.030 mass.%. In the steel samples with TiO2 additions, this value also decreases from 49.05% to 36.26% as the sulfur content increases. The nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 34 publications
(46 reference statements)
2
58
0
Order By: Relevance
“…They mostly used artificially added oxide powders like Ti 2 O 3 to create the desired inclusion types because an appropriate tailoring of potent nucleation sites only by deoxidation and desulfurization reactions can be difficult. [21][22][23] However, this might be in contrast to the demands of high-quality steels, which generally require low inclusion contents. The present study investigates the acicular ferrite formation on nonmetallic inclusions on a laboratory scale, with special consideration paid to the importance of the relationship between steel composition and inclusion type.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…They mostly used artificially added oxide powders like Ti 2 O 3 to create the desired inclusion types because an appropriate tailoring of potent nucleation sites only by deoxidation and desulfurization reactions can be difficult. [21][22][23] However, this might be in contrast to the demands of high-quality steels, which generally require low inclusion contents. The present study investigates the acicular ferrite formation on nonmetallic inclusions on a laboratory scale, with special consideration paid to the importance of the relationship between steel composition and inclusion type.…”
Section: Introductionmentioning
confidence: 61%
“…Mu et al [21] and Xuan et al [22] investigated different steel grades with carbon contents between 0.2 and 0.3 wt pct. They mostly used artificially added oxide powders like Ti 2 O 3 to create the desired inclusion types because an appropriate tailoring of potent nucleation sites only by deoxidation and desulfurization reactions can be difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grong et al suggested that a specially designed master alloy containing the inclusions could be added into the liquid steel directly. This possibility has been utilized to study, e.g., the formation of IGF in cast plain carbon steel inoculated by Ti‐oxide nanopowders and ferrite formation in steels where Ti 2 O 3 , TiO 2 , and TiN particles were added directly to the molten steel . The details of the decomposition of austenite are essential, and it is important to have profound knowledge of the phase transformations, including, e.g., the starting temperature of GBF and IGF formation (T GBF,s and T IGF,s ) since it can be used to control the final microstructure and thus the steel properties.…”
mentioning
confidence: 99%
“…1) In contrast, fine dispersed oxides may act as inoculants for the heterogeneous nucleation of complex inclusions. These inclusions may finally be active for grain refinement during solidification 2,3) and for the control of microstructure formation in the solid state [4][5][6] just to name two examples. The adjustment of oxides to act as inoculants was recognized in the 1980s 7,8) and termed "oxide metallurgy".…”
Section: Introductionmentioning
confidence: 99%